The risk factors of plasma transfusions during resuscitation in pediatric burn patients: a retrospective study from 2010 to 2021 - Zhu, Liqiang; Zhang, Xiaorong; Wang, Xingcun; Zhang, Haiwei; Chen, Pengju; Zhang, Guangfeng; Gao, Peigang (Frontiers in Pediatrics, 2025)
ObjectivesTo analyze the prevalence and risk factors of plasma transfusions during resuscitation after burns in children.MethodsA retrospective study was carried out at the Burn Treatment Center of the Central Theatre Air Force Hospital of the People's Liberation Army in Datong City, China. The study included pediatric patients (between the ages of two months and 14 years) who were admitted for burns between January 2010 and December 2021. Details of plasma transfusions during the burn resuscitation process for each child were recorded. The association between risk factors and plasma transfusions was evaluated using non-conditional logistic regression.ResultsOf the children who suffered from burns, 12.89% (n = 174/1,350) received plasma transfusions during burn resuscitation. The median amount of plasma transfusions administered was 2.5 units (interquartile range, 1.4). Among the pediatric burn patients who received plasma transfusion, 67.24% did not receive any treatments before being admitted to the hospital, while 14.94% were admitted 6 h or more after the burns occurred. The total body surface area (TBSA) of pediatric burn patients who received plasma transfusion ranged from 10% to 55%, with a median burn area of 20% of the TBSA and a mean burn area of 22% of the TBSA. Non-conditional logistic regression analysis identified TBSA, white blood cell count (WBC), heart rate, and pre-hospital remedies as significant predictors of plasma transfusion.ConclusionTBSA (total body surface area), WBC (white blood cell count), heart rate, and pre-hospital interventions can serve as reliable predictors for determining the necessity of plasma transfusions during burn resuscitation. Utilizing these factors can assist blood banks and clinicians in preparing and administering targeted plasma treatments, as well as potentially reducing the overall need for plasma transfusions in pediatric burn patients.